(untitled) (AYUSHDHARA, 2025)
Fistula-in-Ano (Bhagandara) is a challenging anorectal disorder marked by chronicity, recurrence, and potential complications like incontinence. Ayurvedic texts classify it among the Ashta Mahagada (eight grave diseases). Ayurveda offers Kshara Sutra therapy as a minimally invasive alternative. Case Presentation: A 30-year-old male presented with a recurrent perianal fistula. He had a history of incision and drainage in 2017, and laser fistulectomy in sept 2023. Magnetic resonance imaging (MRI) fistulography identified a trans-sphincteric fistulous tract with the internal opening located at the 6 o’clock position. The patient was successfully managed at our hospital using the minimal invasive ayurvedic IFTAK technique (Interception of Fistulous Tract with Application of Kshara Sutra). Intervention and Outcome: The IFTAK technique involves identifying the fistulous tract and creating a controlled window at the intersphincteric plane. Through this window, the tract was intercepted, and a medicated Kshara Sutra (alkaline seton) is selectively applied to the remaining portion of the tract. Postoperative management included weekly replacement of the medicated thread, sitz baths, local application of Jatyadi Taila, and administration of oral Ayurvedic medications. Complete healing of the fistulous tract was achieved within five weeks. No recurrence or postoperative complications were observed during an 18-month follow-up period. Conclusion: The IFTAK technique, when integrated with Ayurvedic interventions, provides a safe and effective approach for the management of complex or recalcitrant fistula-in-ano. This sphincter-conserving method is associated with reduced postoperative pain, promoting controlled healing and drainage, lower recurrence rates, and shorter hospital stays. Further studies are recommended to establish its broader clinical utility.